The effect of calcium carbonate nanofiller on the mechanical properties and crystallisation behaviour of polypropylene - Hanim, H.; Zurina, R.; Ahmad Fuad, M. Y.; Mohd. Ishak, Z. A.; Hassan, Azman (Plastics and Rubber Institute of Malaysia, 2008)

(untitled)
Polypropylene/calcium carbonate (PP/NPCC) nanocomposites were prepared using a co-rotating twin screw extruder at filler loadings of 5, 10 and 15 weight %. The impact strength and modulus of PP showed some improvement with the incorporation of the nanofiller while the tensile strength deteriorated. SEM photomicrographs showed evidence of NPCC agglomeration within the PP matrix, indicating that the level of shear stress generated during melt compounding was far from adequate to break-up the nanofiller. WAXD results showed the appearance of Î²-phase PP in the nanocomposites with 10 and 15 weight % NPCC. The influence of NPCC filler on the crystallisation behaviour of PP were also investigated using a DSC. Incorporation of NPCC shifted the crystallisation exotherms of PP towards higher temperatures, indicating that the nanofiller has acted as a nucleating agent for PP. The reduced values of half crystallisation times also implied that the introduction of NPCC has accelerated the crystallisation rate of PP.